Chaotic dynamics in memristive circuits - Kelly C. Iarosz; Enrique C. Gabrick; José Trobia; Rafael R. Borges; Paulo R. Protachevicz; Robson C. Bonetti; Silvio L.T. de Souza; Gabriel L. Batista; José D. Szezech Jr.; Iberê L. Caldas; Antonio M. Batista (Revista Brasileira de Ensino de Física, 2023)
Memristors (abbreviation of memory and resistor), introduced as the fourth fundamental electrical circuit element, remember the electric charge that flowed through it. These nonlinear elements are considered as a class of two terminal resistive devices and offers a lot of possible applications in various areas. In this article, we review the dynamical behaviour of some electrical circuits with memristors. Initially, we show that a simple circuit with a capacitor and an inductor connected to a memristor exhibits periodic and chaotic attractors. After that, we show that the known Chua circuit, with a nonlinear resistance, can generate bifurcations and chaos. Substituting the nonlinear resistance by a memristor, the modified Chua circuit exhibits coexistence of attractors. Another known circuit, the Colpitts, is made of a combination of capacitors and inductors containing a bipolar junction transistor. We show that the modified Colpitts circuit, created by substituting the transistor by a memristor, presents multistability and coexistence of many attractors.